The Rational and Irrational Dialectics in the Simulacrum of Posters and Narratives in Indonesian Horror Film Genre - Triartanto, A. Yudo; Mutiah, Tuty; Suriyanto, Adhi Dharma; Hamid, Ali Imron; Fitri, Syarif (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
In recent years—and even dating back to the 1970s and 1980s—the Indonesian horror film genre has consistently drawn large audiences to theaters. Conceptually, this study examines this phenomenon by employing Max Horkheimer’s theory of rational and irrational dialectics, Jean Baudrillard’s concept of simulacrum, and Textual Analysis applied to horror film posters and narratives from the 1970s to the 2000s, alongside select Asian horror films that resonate with audiences. The rational and irrational dialectic emerges prominently in Indonesian horror films, as viewers grapple with the interplay between reality and the supernatural depicted in posters and narratives that serve as simulacra, ultimately becoming modern myths. Philosophically, this dialectic presents a dilemma where humans navigate rationality and irrationality in attempting to dismiss mythological elements. Simulacrum, in this context, represents a duplication without an original, blurring the line between the copy and the real. Textual Analysis, rooted in media and cultural studies, is employed here as a methodology for examining texts that contain meaningful signs. Most Indonesian horror film posters and narratives feature terrifying creatures without real-world references. As a result, despite a dip in popularity during the 1990s, horror films from the 1970s through the 2000s have frequently achieved high viewership, especially those based on legendary tales familiar to audiences. These recurring themes, perpetuated through film posters and narratives, are further reinforced by makeup, animation techniques, and CGI (Computer Generated Imagery), all of which bring the horror elements to life.